Clinical and Polysomnographic Comparison of Patients with Rapid Eye Movementdependent and Positional Obstructive Sleep Apnoea Syndromes - Vasfiye Kabeloğlu (Türk Uyku Tıbbı Dergisi, 2021)

(untitled)
Objective:In this study, we aimed to compare the clinical and polysomnographic features of rapid eye movement sleep-dependent obstructive sleep apnoea syndrome (REM-OSAS) and positional OSAS (pos-OSAS).Materials and Methods:This study included all patients diagnosed with REM-OSAS and pos-OSAS who were examined at our sleep and disorders unit between January 2019 and November 2020. All patients underwent a full-night polysomnographic examination.Results:A total of 300 patients with OSAS were included in the study, of which 60 (20%) were diagnosed with REM-OSAS and 75 (25%) with pos-OSAS. REM-OSAS had a female predominance, whereas pos-OSAS demonstrated a male predominance (p<0.001). Body mass index was significantly higher in patients with REM-OSAS than in those with pos-OSAS (p=0.003). OSAS severity was found to be higher in patients with pos-OSAS than in those with REM-OSAS (apnoea-hypopnea index: 23/hour, p<0.001). The supine and REM sleep pulse rates were significantly higher and the minimum oxygen saturation level was significantly lower in patients with REM-OSAS than in those with pos-OSAS (p<0.001, p=0.010).Conclusion:The results of this study revealed that OSAS severity was higher in patients with pos-OSAS than in those with REM-OSAS. Body position plays a more significant role than sleep stage on OSAS severity. REM-OSAS was more common in female patients, whereas pos-OSAS had a male predominance. Patients diagnosed with REM-OSAS had a significant tendency to be overweight. Oxygen saturation was lower in patients with REM-OSAS than in those with pos-OSAS.